Rare complications of cesarean scar - Mahajan, Divyesh; Kang, Mandeep; Sandhu, Manavjit Singh; Jain, Vanita; Kalra, Naveen; Khandelwal, Niranjan (Indian Journal of Radiology and Imaging, 2013)
Cesarean scar pregnancy (CSP) and cesarean scar dehiscence (CSD) are the most dreaded complications of cesarean scar (CS). As the incidence of CS is increasing worldwide, so is the incidence of CSP, especially in cases with assisted reproduction techniques. It is of utmost importance to diagnose CSP in the early first trimester, as it can lead to myometrial rupture with fatal outcome. On the other hand, CSD may be encountered during pregnancy or in the postpartum period. CSD in the postpartum period is very rare and can cause secondary postpartum hemorrhage (PPH) leading to increased maternal morbidity or even death if not diagnosed and managed promptly. Both complications can be diagnosed on ultrasonography (USG) and confirmed on magnetic resonance imaging (MRI). These two conditions carry high morbidity and mortality. In this article, we highlight the role of imaging in the early diagnosis and management of these conditions.
Keywords: Cesarean scar dehiscence; cesarean scar pregnancy; magnetic resonance imaging; ultrasonography